The Relevance of Paulo Freire's Conscientization in Islamic Religious Education Practice - Sulistiono Shalladdin Albany; Muhammad Farhan Al Yuflih; Abdullah Rofi; Faatikhah Arrum Nur Hidayah (Bulletin of Pedagogical Research, 2024)
This study investigates the relevance of Paulo Freire’s concept of conscientization within Islamic religious education. In many traditional Islamic educational institutions, teaching methods are still heavily rooted in rote memorization and authoritative instruction, with minimal space for critical engagement, dialogical learning, and social reflection. This condition poses a challenge to the goal of Islamic education, which is to form holistic individuals who are spiritually devout, ethically responsible, and socially aware. Freire’s educational philosophy, which promotes dialogical methods, problem-posing strategies, and praxis—the union of reflection and action—offers a transformative pedagogical framework that can be integrated with Islamic values. Through a qualitative library research method, this study analyzes selected scholarly literature from 2018 to 2023, focusing on works related to critical pedagogy, Islamic educational reform, and humanistic learning. The findings demonstrate strong philosophical and pedagogical parallels between Freire’s conscientization and core Islamic concepts such as ta’dib, ijtihad, shura, and amar ma’ruf nahi munkar. While Freire’s secular-humanist orientation may raise theological concerns, this study shows that with contextual adaptation, his ideas can enrich Islamic pedagogy rather than contradict it. The study proposes the development of an “Islamic critical pedagogy” that synthesizes Freirean methodology with Islamic ethical foundations. Such integration can revitalize Islamic education by promoting critical thinking, moral consciousness, and active citizenship among learners. Ultimately, the research contributes to the discourse on educational reform in Muslim societies by offering a pedagogical model that is both theologically grounded and socially transformative.